Pengembangan aplikasi kesehatan ibu dan balita berbasis web untuk Puskesmas - Jalang, Yohanes Kurniawan; Pramaditya, Himawan (Universitas Merdeka Malang, 2023)
Puskesmas manages the Posyandu which acts as a forum for monitoring the growth of toddlers and the health of mothers. Posyandu holds routine activities ranging from weighing, immunization, to consultations, where the data obtained is recorded in the â€œKartu Menuju Sehatâ€ book. The process of recording data that is still done manually can risk causing problems such as errors in data collection. This study aims to update the data management system for Posyandu by digitizing it using the Waterfall method approach. The web-based application was developed in order to assist Posyandu cadres in the data management process while at the same time facilitating Puskesmas staff in efforts to control malnutrition. In addition, this application can be an alternative to filling out the â€œKartu Menuju Sehatâ€ book, thereby facilitating the child growth recapitulation process. The child's growth report will be recorded in the system after the toddler carries out an examination at the Posyandu and the cadre fills in the toddler's examination data. Cadres can then arrange the Posyandu implementation schedule and immunization list for the next period. Through the application developed, Posyandu cadres can collect data on mothers and toddlers and can manage data more easily and quickly.